Investor Relations and Private Debt Markets - Chapman, Kimball L.; Lee, Ruby; Reiter, Nayana; Williams, Christopher D. (The Accounting Review, 2025)
ABSTRACT We examine the role of investor relations (IR) in private debt markets. We find that firms with dedicated IR officers (IROs) receive significantly lower loan spreads, particularly when lenders require a better understanding of the borrower’s risk profile. Among firms with IROs, those with longer tenured officers experience lower spreads, especially when IROs also manage financial responsibilities. To address endogeneity concerns, we demonstrate that loan spreads decline when a firm establishes an IR program and rise when the program is discontinued. Furthermore, when a different individual assumes the IRO role, loan spreads increase, even though there are no reductions in firm disclosure. Loans issued to firms with IROs also have shorter syndication duration, attract more nonrelationship, foreign, and nonbank participant lenders, feature more customized covenants, and are less likely to undergo renegotiation. Overall, our study provides robust evidence of the relevance of IR in private debt markets. JEL Classifications: D82; G14; G21; G32; M41.